Chemical and Physical Approaches for the Treatment of Alzheimer's Disease - Jing Li; Wei Zhou; Xiaoli Wu; Kin Tam (International Association of Physical Chemists (IAPC), 2015)
Alzheimer's disease (AD) is a destructive neurodegenerative disorder, which threatens elderly people in their mental health irreversibly, causing cognitive deficit such as learning difficulties and memory loss. Neurobiological pathogenesis leading to the neuronal dysfunction in AD are mainly rationalized by two hypotheses: 1) extracellular aggregation of the β-amyloid (Aβ) peptide, which impacts on the normal neuronal pathways through excessive oxidative stress and damages neurons; and 2) intracellular hyperphosphorylation of tau protein, which forms the paired helical filaments, then gravely impacts axonal transport. In this review, we firstly introduce the neurobiological concept of AD, and its pathogenesis. Then we review the chemical approaches pointedly directing at Aβ peptide and tau protein, and the clinical reality of these pharmacological strategies. Thirdly, we discuss a physical approach, deep brain stimulation (DBS), which is receiving considerable attention in recent years due to its success in treating Parkinson disease clinically. DBS delivers current pulses, which are generated by a implanted pacemaker, through electrodes into dysfunctional brain structures to influence neural activities with the possibility to improve the cognitive function. We will summarize the clinical applications of DBS to restore cognitive impairments due to AD, and animal studies related with DBS. Finally, we will discuss the current study obstacles and future research development of DBS in preclinical and clinical investigations of AD.